(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Life itself shows that it is necessary to raise the human factor through the issue of achieving justice in the legal system, ensuring citizens’ confidence in the future, impartial assessment of the activities of state bodies. "Holy Motherland, to defend it is an honorable duty!" put forward important principles of the idea and factors of civic duty.